Identifying the Meaning of a Textual Theme through a Song Based on Halliday's Perspective - Nguyen Van Thao; Ridwin Purba (Journal of English Language and Education, 2021)
The study is aimed to find out the textual theme meaning from the song lyrics. The problem raised in this research: What kinds of thematic meaning found in the song lyrics of “Always” by Bon Jovi?. To answer the problem, the researchers applied qualitative research. The content analysis method was adapted in this research. The method of collecting data, the researchers used documentation and literature study. The data source is the song lyrics of the “Always” song lyrics. The results of this research show that there are 64 data. The researchers finds four types are: (1) 33 data to Interjection, (2) 10 data to Causal , (3) 8 data to Additive, (4) 13 data to Adversative. The percentages in Always song lyrics are: (1) 51,56 % to Interjection (2) 15,62 % Causal, (3) 0 for Conditional, (4) 12,5 % to Additive, (5) 20,31 % to Adversative. This result of result is hoped to be useful for those who are interested in learning about functional grammar.